Cultural Identity and Social Interaction of Indigenous Peoples in the Middle of Modernization (Case Study of Indigenous Peoples of Kasepuhan Banten Kidul) - Malik, Abdul (Jurnal The Messenger, 2018)
The indigenous community of Kasepuhan Banten Kidul is society entity that still maintains the past Sundanese traditions strictly, but is quite open and adaptive to the development of the age. The condition is reflected in their accommodative attitude towards all social changes that occur due to modernization. However, this condition does not make them lose their cultural identity as kasepuhan community. In the social interaction, the cultural identity is always inherent in them, both in the way of acting or reacting, and symbolized through the clothes and accessories worn. This condition can not be separated from the existence of indigenous institutions that have central role in upholding indigenous rules, so that all members of kasepuhan community have so strong ties to their cultural identity. Therefore, although in always changing social situation, they are able to adapt and even adopt the changes by not losing their cultural identity.